REHABILITATION POTENTIAL AS THE BASIS OF THE PROCESS OF RESOCIALIZATION AND SOCIAL ADAPTATION OF YOUNG PERSONS AFTER ISCHEMIC STROKE (Literature Review) - Kim Olga Anatolevna, (EPRA International Journal of Research and Development (IJRD), 2023)
Nowadays stroke is still a completely unresolved problem of the modern medical community, leading to a high percentage of death, and in case of survival - to disability. Disability after suffering a brain accident occupies a leading position among all causes of disability in patients, which significantly worsens the quality of life of patients and complicates the process of their resocialization and social adaptation. This article is devoted to the concept, principles and criteria of rehabilitation potential, as well as factors influencing it.